1964
DOI: 10.1071/ch9640787
|View full text |Cite
|
Sign up to set email alerts
|

Acetoxylation by aryliodoso acetates. III. Effects of structural changes in the reactants

Abstract: Definite increases in rate of reaction between aryliodoso acetates and N-arylacetamides occur when electron-releasing groups are introduced into the N-arylacetamide nucleus, the Arrhenius A and E parameters decreasing simultaneously; electron-attracting substituents cause the reverse effects. Small, erratic changes in rate and the Arrhenius parameters accompany substitution in the aryliodoso nucleus. N-Methylation of aceto-p-toluidide inhibits the reaction completely. Possible mechanisms are briefly discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1977
1977
2002
2002

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Under milder reaction conditions (ice cooling, 10 min), 2i − 2 was obtained in 41% yield along with 2i − 1 (20%) (entry 6). This indicates that a trifluoroacetoxy group attacks the ipso position first and subsequently migrates to the meta position, as was the case with the reaction of 1i with PIDA in acetic acid 3a…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…Under milder reaction conditions (ice cooling, 10 min), 2i − 2 was obtained in 41% yield along with 2i − 1 (20%) (entry 6). This indicates that a trifluoroacetoxy group attacks the ipso position first and subsequently migrates to the meta position, as was the case with the reaction of 1i with PIDA in acetic acid 3a…”
Section: Resultsmentioning
confidence: 79%
“…However, acetanilides having electron-donating substituents, such as methoxy or methyl, at the para position react with PIDA in acetic acid to give high yields of m -acetoxy derivatives . Nair et al investigated the mechanism of this reaction and found that it involves an electrophilic displacement that results in direct transfer of an acetoxy group to the para position and subsequent intramolecular migration to the meta position . Following these early reports, very little has been published regarding reaction of acetanilide and PIDA or phenyliodine(III) bis(trifluoroacetate) (PIFA).…”
Section: Introductionmentioning
confidence: 99%